Kajian pelaksanaan (PPIA) pada ANC oleh bidan di Bidan Praktek Mandiri - Inka Kartika Ningsih; Sumarah Sumarah; Sari Hastuti (Poltekkes Kemenkes Yogyakarta, 2015)
Kota Yogyakarta is the highest city with peoplewho suffer HIV/AIDS in DIY. In 2013, DIYAIDS prevalence is 23, 75%. In DIY, ODHA has touched 72,6%, based ton age class 25-49 years old peak. PPIA programs is done to prevent HIV to infect children rom their mother. This research was categorized into qualitative descriptive researchs which have implement grounded theory. This research was conducted in BPM in Kota Yogyakarta on Maret-June 2014. The subject of the research was 5 midwifes in BPM, mother pregnancy patient of the BPM, midwife coordinator of primary public heatlh care center, and family health care sector in health careDepartment of Kota Yogyakarta. The first responden has been taken a sample by snowball sampling. Research instrument is human instrument and the data is collected with in depth interview. Data analysis is done using content analysis and data validation using triangle source. PPIA in midwife practices is prevent HIV on reproductive female. Themother pregnancy have been send to get ANC Terpadu in primary public health conter.Research result is that PPIA in ANC doesn't work effective in BPM Yogyakarta because PPIA can't work their program without midwife and primary public health center.